Effect of food-based and iron-folic acid (IFA) supplementation on nutrient intakes in pregnant women - Meisara, Naura Delfi; Fahmida, Umi; Laily, Noer (World Nutrition Journal, 2025)
Nutrient deficiencies during pregnancy are worsened by poor intake and low adherence to supplementation. This study aimed to assess the impact of a food-based intervention using soy-hydrolysate and iron-folic acid (IFA) supplementation on the nutrient intake of pregnant women. This study aimed to assess the impact of a food-based intervention using soy-hydrolysate and iron-folic acid (IFA) supplementation on the nutrient intake of pregnant women